Analisis Kesalahan Penggunaan Huruf Kapital dan Tanda Baca pada Hasil Menulis Siswa Kelas V Sekolah Dasar Negeri 67 Kota Bengkulu - dzihni fitrah; Resnani Resnani; neza agusdianita (Universitas Bengkulu, 2021)
ABSTRACTThe aims of this research were to describe the errors in the use of capital letters, punctuation marks and commas in the invitation letters for fifth grade students at the State Elementary School 67 Bengkulu City. This research used descriptive qualitative method. The research subjects were students VC grade. The data were collected through documentation.The data analysis technique used language error analysis, validity test increases persistence and member checks. The result showed that the keys to using capital letters were found at the beginning of sentences (18.72%), names of people (45.41%), names of years, months, holidays and historical events (43.97%), geographic names (27, 72%), not abbreviated titles, ranks and greetings (32.69%). Errors in the use of signs were found at the end of sentences (60%), separating the hours, minutes, and seconds (17%), not being used after the sender, recipient, and letter date (3%). Incorrect use of commas was found between names and addresses, parts of addresses, places and dates (80%), between names of persons and abbreviations of academic degrees that follow (59%), behind the caption at the beginning of the sentence (53%).